Teaching of Physics Courses in Epochs of Pandemic: Tablet versus Blackboard - Nieto-Chaupis, Huber (2022)
Because the pandemic of Covid-19, lectures and classes have demanded to employ the latest technologies to present an educational session as an online session. For example, universities courses have required that instructors have kept the quality of teaching by employing electronic tools that to some extent can replace the classical blackboard with a high fidelity. In this manner, mostly educators have used electronic tablets as e-blackboard, particularly when mathematical and physics are passing through the chapters where equations and specific demonstrations of equations are needed to convince students some laws of nature. This paper discusses in a quantitatively manner the usage of tactile technologies to teach Physics in pandemic epochs.